Book of proceedings and abstracts - Chesney, Patrick, Dr., proceeding ed. (2016)
Aims to foster and develop education and research in all disciplines contributing to the knowledge and stewardship of the biodiversity of the Guiana Shield and the conservation, preservation, and sustainable management of its natural, rural and urban ecosystems.